Pekinenin E Inhibits the Growth of Hepatocellular Carcinoma by Promoting Endoplasmic Reticulum Stress Mediated Cell Death - Fan, Lu; Xiao, Qingling; Chen, Yanyan; Chen, Gang; Duan, Jinao; Tao, Weiwei (Frontiers in Pharmacology, 2017)
Hepatocellular carcinoma (HCC) is a malignant primary liver cancer with poor prognosis. In the present study, we report that pekinenin E (PE), a casbane diterpenoid derived from the roots of Euphorbia pekinensis, has a strong antitumor activity against human HCC cells both in vitro and in vivo. PE suppressed the growth of human HCC cells Hep G2 and SMMC-7721. In addition, PE-mediated endoplasmic reticulum (ER) stress caused increasing expressions of C/EBP homologous protein (CHOP), leading to apoptosis in HCC cells both in vitro and in vivo. Inhibition of ER stress with CHOP small interfering RNA or 4-phenyl-butyric acid partially reversed PE-induced cell death. Furthermore, PE induced S cell cycle arrest, which could also be partially reversed by CHOP knockdown. In all, these findings suggest that PE causes ER stress-associated cell death and cell cycle arrest, and it may serve as a potent agent for curing human HCC.